2009
DOI: 10.1080/13576500802233722
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the preferred neck-resting position of Caribbean flamingos (Phoenicopterus ruber)

Abstract: When resting, flamingos often lay their heads along their backs. While in this position they must curve their necks to either the right or left of their midline. Observations of captive Caribbean flamingos at the Philadelphia Zoo (Philadelphia, PA, USA) were conducted in order to determine if individual birds would display consistent preferences in neck-resting position over multiple observations. While individual birds were shown to vary greatly in regards to the strength and direction of their preferences, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…Similarly, individual binomial tests comparing the observed instances of resting while standing on the right and left leg for each bird failed to reveal significant lateral biases at the level of the individual (P40.05, two-tailed). Thus, it can be concluded that, unlike their own neck resting behavior [Anderson et al, 2009], and the preferred resting leg stances of several other bird species [Randler, 2007], Caribbean flamingos do not display individual or group level lateral preferences in leg stance while resting.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, individual binomial tests comparing the observed instances of resting while standing on the right and left leg for each bird failed to reveal significant lateral biases at the level of the individual (P40.05, two-tailed). Thus, it can be concluded that, unlike their own neck resting behavior [Anderson et al, 2009], and the preferred resting leg stances of several other bird species [Randler, 2007], Caribbean flamingos do not display individual or group level lateral preferences in leg stance while resting.…”
Section: Resultsmentioning
confidence: 98%
“…First, we sought to determine whether flamingos resting on one leg display individual or flock level lateral preferences in leg stance. As we have recently shown both individual and flock level lateral preferences in neck resting position, with most birds preferring to curve their necks to the right of their bodies when resting their heads on their backs [Anderson et al, 2009] (see Fig. 1), such preferences in leg stance seemed possible.…”
Section: Study 2: the Influence Of Lateral Preferences Resting Locatmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to achieve this positioning they curve their necks to either the right or left of their midline. Previously we have shown both individual and flock-level laterality of preferred neck-resting direction, with most birds preferring to rest their necks to their right (Anderson, Williams, & O'Brien, 2009). As laterality has been shown to play a role in social cohesion (e.g., Rogers & Workman, 1989) and aggression (e.g., Vallortigara, Cozzutti, Tommasi, & Rogers, 2001), here we attempted to determine whether a flamingo's preferred neck-resting direction could be used to predict involvement in aggressive encounters.…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…In a recent study we tested for potential lateral asymmetry in the resting behaviours of Caribbean flamingos (Phoenicopterus ruber) (Anderson et al, 2009). When flamingos rest they lay their heads on their backs.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%